2004
DOI: 10.1002/jcp.20060
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones regulate DNA‐synthesis and cell‐cycle proteins by activation of PKCα and p42/44 MAPK in chick embryo hepatocytes

Abstract: The molecular mechanism by which thyroid hormones exert their effects on cell growth is still unknown. In this study, we used chick embryo hepatocytes at different stages of development as a model to investigate the effect of the two thyroid hormones, T3 and T4, and of their metabolite T2, on the control of cell proliferation. We observed that T2 provokes increase of DNA-synthesis as well as T3 and T4, independently of developmental stage. We found that this stimulatory effect on the S phase is reverted by spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 52 publications
(44 reference statements)
2
26
0
3
Order By: Relevance
“…Since tyrosine phosphorylation is important for PKC activity (Tapia et al, 2002;Pula et al, 2005), these data suggest that the inhibition of T 3 -induced tail regression may be through alteration of tyrosine kinase signaling. This is consistent with the observations that T 3 or T 4 enhances kinase activity of PKC in the chick embryo (Alisi et al, 2004) and that the PKC inhibitor, H7, inhibits T 3 (Fig. 8A) or T 4 -induced tadpole tail regression (Petcoff and Platt, 1992;Phillips and Platt, 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since tyrosine phosphorylation is important for PKC activity (Tapia et al, 2002;Pula et al, 2005), these data suggest that the inhibition of T 3 -induced tail regression may be through alteration of tyrosine kinase signaling. This is consistent with the observations that T 3 or T 4 enhances kinase activity of PKC in the chick embryo (Alisi et al, 2004) and that the PKC inhibitor, H7, inhibits T 3 (Fig. 8A) or T 4 -induced tadpole tail regression (Petcoff and Platt, 1992;Phillips and Platt, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…The pathways involved include those mediated by tyrosine kinases (Di Fulvio et al, 2000;Utoh et al, 2003;Martinez and Gomes, 2005), protein kinase C (PKC) (Petcoff and Platt, 1992;Phillips and Platt, 1994;Wagner et al, 2001;Alisi et al, 2004), mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) (Lin et al, 1997(Lin et al, , 1998(Lin et al, , 1999aDavis et al, 2000;Bergh et al, 2005), cyclin-dependent kinases (Barrera-Hernandez et al, 1999;Nguyen et al, 2003;Skirrow, 2003;Skirrow and Helbing, 2007), and phosphatidylinositol-3 kinase (PI3K) (Lei et al, 2004;Cao et al, 2005;. However, the precise target substrates, the location of phosphorylation sites, their integration into the TH signaling pathway, and functional roles in specific tissues remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous studies in HeLa cells, CV-1 monkey fibroblasts and chick embryo hepatocytes that have demonstrated the ability of thyroid hormones to activate the MAPK signalling cascade and promote the phosphorylation of ERK within 5-20 min after treatment (Lin et al 1999, Alisi et al 2004, Bergh et al 2005. We used concentrations of T 3 and T 4 that were reported previously to produce the maximal ERK activation response in other cell types.…”
Section: Discussionsupporting
confidence: 90%
“…However, these studies were performed in rat osteoblast cell lines and used only T 3 (and not T 4 ) at a very high concentration of 100 nM for 30 min. Thus, there may be species differences in response, or as reported previously (Lin et al 1999, Alisi et al 2004, Bergh et al 2005, thyroid hormone effects on ERK activation are rapid and transient with activation returning to control levels by 30 min.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation